1992
DOI: 10.1007/bf02280765
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ofloxacin in elderly patients and in healthy young subjects

Abstract: The pharmacokinetics of ofloxacin, a fluoroquinolone widely used in the treatment of bacterial infections, may be different according to age, owing to the biological differences that exist between an elderly organism and a young subject, especially as regards the renal and the hepatic function. In our study the pharmacokinetics of ofloxacin in 12 elderly patients was found to be different from those of 12 healthy young volunteers. The elimination half-life (t1/2) was slightly shorter in the young subjects than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Ofloxacin is renally eliminated and clearance of this drug is decreased by aging in humans, with oral clearances in healthy young, healthy elderly and elderly patients with no impairment of renal function of 233, 169 and 83.3 mL/min, respectively (Molinaro et al, 1992;Rademaker et al, 1989). Since the bioavailability of ofloxacin in young subjects is >95% (Lode et al, 1987), the decrease in clearance is thought to be caused by reduced renal clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ofloxacin is renally eliminated and clearance of this drug is decreased by aging in humans, with oral clearances in healthy young, healthy elderly and elderly patients with no impairment of renal function of 233, 169 and 83.3 mL/min, respectively (Molinaro et al, 1992;Rademaker et al, 1989). Since the bioavailability of ofloxacin in young subjects is >95% (Lode et al, 1987), the decrease in clearance is thought to be caused by reduced renal clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Similar biexponential declines in diazepam plasma levels have been found after dosing in dogs and monkeys (Curry et al, 1977;Klotz et al, 1976). Ofloxacin is a renally eliminated drug that shows decreased clearance with aging in humans (Molinaro et al, 1992) and is also similarly cleared by the kidney as the unmetabolized form in monkeys and dogs (Okazaki, 1984;Sudo et al, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…ings have suggested that the volume of distribution and total body clearance of a number of fluoroquinolones including ofloxacin might be affected by age and/or gender (1,4,6,12,13). For ofloxacin, following multiple 200-mg doses of ofloxacin administered every 12 h, significant accumulation was noted among elderly patients, whereas C max , AUC, and elimination half-life did not increase in younger patients following 7 days of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of many drugs are altered by age (14) and/or by gender (9). Molinaro et al (6) reported that, compared with healthy young subjects, the elimination of ofloxacin was delayed in elderly patients. The objective of this study was to evaluate the influence of age and gender on the pharmacokinetics of levofloxacin in healthy subjects.…”
mentioning
confidence: 99%
“…Ofl oxacin and ciprofl oxacin are applied in the treatment of infections outside the urinary tract because they have much lower minimum inhibitory concentrations against sensitive organisms than their predecessors, such as nalidixic acid [1,2] . During the past decade, there has been a growing interest in obtaining adequate information about the effects of fl uoroquinolones in humans [3][4][5][6] as well as in women in comparison with men [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%